2023
DOI: 10.1128/jvi.01423-22
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of the RIG-I/MDA5 Signaling Pathway upon Influenza D Virus Infection Impairs the Pulmonary Proinflammatory Response Triggered by Mycoplasma bovis Superinfection

Abstract: Since the spread of the respiratory influenza D virus (IDV) infection to the cattle population, the question about the impact of this virus on bovine respiratory disease (BRD) remains still unanswered. Animals affected by BRD are often coinfected with multiple pathogens, especially viruses and bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“… 2021 ; Gaudino et al. 2023 ). In France, Mycoplasma bovis is the most frequently isolated etiologic agent in these BRDC outbreaks, spreading early and widely throughout the affected units (60–100% isolation rate and seroconversion) (Arcangioli et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2021 ; Gaudino et al. 2023 ). In France, Mycoplasma bovis is the most frequently isolated etiologic agent in these BRDC outbreaks, spreading early and widely throughout the affected units (60–100% isolation rate and seroconversion) (Arcangioli et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2020 ; Gaudino et al. 2023 ), especially for young feedlot calves, ranging from 30% in Belgium (van Leenen et al. 2020 ), to 49% in Switzerland, and up to 90% in the U.S.A (Hilton 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that clinical signs and susceptibility to secondary bacterial infection with Mannheimia haemolytica in calves are not increased by a primary infection with IDV [ 26 ], calves co-infected with IDV and Mycoplasma bovis suffer from a more severe respiratory disease than those infected with either at the same condition [ 31 ], implying that IDV may facilitate certain coinfections within the BRD complex. Further research found that IDV was likely to trigger immune pathways that inhibited the innate immune response against the bacteria, which resulted in an increased susceptibility to the secondary bacterial infection in cattle [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IDV co-infection increased the replication of M. bovis . The interaction between IDV and M. bovis was additionally studied in ex vivo models using precision-cut lung slices by Gaudino et al [ 18 ]. The results suggested that a primary IDV infection promoted M. bovis superinfection by increasing bacterial replication and by causing damage to lung pneumocytes.…”
Section: Introductionmentioning
confidence: 99%